Dissection for Floral Micromorphology and Plastid Genome of Valuable Medicinal Borages Arnebia and Lithospermum (Boraginaceae) - Park, Inkyu; Yang, Sungyu; Song, Jun-Ho; Moon, Byeong Cheol (Frontiers in Plant Science, 2020)
The genera Arnebia and Lithospermum (Lithospermeae-Boraginaceae) comprise 25–30 and 50–60 species, respectively. Some of them are economically valuable, as their roots frequently contain a purple-red dye used in the cosmetic industry. Furthermore, dried roots of Arnebia euchroma, Arnebia guttata, and Lithospermum erythrorhizon are used as traditional Korean herbal medicine. In the absence of a comparative (micro)morphological and genomic study, these different medicinal borages are often treated as a single remedy. Here, we determined the floral micromorphology and complete chloroplast (cp) genome sequences of A. guttata (including Arnebia tibetana), A. euchroma, and L. erythrorhizon. We reveal great diversity in floral epidermis cell patterns, gynoecium, and structure of trichomes. The cp genomes were 149,361–150,465 bp in length, with conserved quadripartite structures. In total, 112 genes were identified, including 78 protein-coding regions, 30 tRNA genes, and four rRNA genes. Gene order, content, and orientation were highly conserved and were consistent with the general structure of angiosperm cp genomes. Comparison of the four cp genomes revealed locally divergent regions, mainly within intergenic spacer regions (atpH-atpI, petN-psbM, rbcL-psaI, ycf4-cemA, ndhF-rpl32, and ndhC-trnV-UAC). To facilitate species identification, we developed molecular markers (PSY, TCY, and NCTV) based on divergence hotspots. High-resolution phylogenetic analysis revealed clear clustering and a close relationship of Arnebia to its Lithospermum sister group, which was supported by strong bootstrap values and posterior probabilities. Overall, gynoecium characteristics and genetic distance of cp genomes suggest that A. tibetana, might be treated as an independent species rather than a synonym of A. guttata. The present morphological and cp genomic results provide useful information for taxonomic, phylogenetic, and evolutionary analysis of Boraginaceae.